Wall painting in the non-canonical typology of the genre-species structure of Chinese fine art - Gao, Xiaotian (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The article deals with a non-canonical art practice in modern Chinese fine art, mural painting of public spaces. The actualization of the above-mentioned problem is caused by the appearance of changes and supplements to the morphological system of Chinese fine art: Chinese state has opened up to the world, dynamic urbanization has begun, the attitude of the society to public spaces and the tasks of mural painting in their visualization have changed. The purpose of the article is to understand the place of modern wall painting in the non-canonical structure of fine art in China at the beginning of the 21st century. The research methodology is based on the methods of both general theoretical analysis and formal-stylistic and compositional-coloristic analysis of works of art. The author analyzes publications in which the state of Chinese and foreign scientific discourse on the specified problem is investigated. Based on the examples of the analysis of the wall painting of Shanghai, Nanjing, Mianyang, and various Chinese villages, the main stylistic, compositional and coloristic means of artistic expressiveness of the murals of the 2020s are determined, and the functional features of modern wall painting as a non-canonical art practice of the latest Chinese fine art are revealed. It has been proven that at the beginning of the 21st century a non-canonical structure of fine art, dialogic in its communicative nature, began to form in the country, which is a part of general processes in the field of modern art. It is stated that today Chinese muralism is in the initial stage of its formation. The study of stylistic, compositional and coloristic means of artistic expressiveness of works of modern wall painting, which appeared at the beginning of the 21st century in China, allows us to assert that the main artistic style of modern wall painting remains realism and its varieties, hyperrealism and photorealism, focused on fairly traditional compositional solutions, but a bright color range. Considering the lack of systematic morphological studies of the fine art of modern China, we believe it necessary to continue analyzing the latest art practices, which today make up the non-canonical structure of the country’s fine art.